Mouse Genome Database (MGD)-2018: knowledgebase for the laboratory mouse. Issue Volume 46:Issue D1(2018) (30th October 2017) - Smith, Cynthia L; Blake, Judith A; Kadin, James A; Richardson, Joel E; Bult, Carol J; ,
Abstract: The Mouse Genome Database (MGD; http://www.informatics.jax.org ) is the key community mouse database which supports basic, translational and computational research by providing integrated data on the genetics, genomics, and biology of the laboratory mouse. MGD serves as the source for biological reference data sets related to mouse genes, gene functions, phenotypes and disease models with an increasing emphasis on the association of these data to human biology and disease. We report here on recent enhancements to this resource, including improved access to mouse disease model and human phenotype data and enhanced relationships of mouse models to human disease.